Genomic Effects of Arginine on Cell Behavior of Conceptus Trophectoderm in Ungulates - Paudel, Sudikshya (J Anim Sci, 2021)
Hatched ungulate (e.g., pigs, sheep and other ruminants) blastocysts undergo dramatic morphological transitions from spherical to tubular to filamentous forms to conceptuses (embryo/fetus and associated extraembryonic membranes) before implantation. L-Arginine (Arg), a conditionally essential amino acid, is required for this process to activate the mTOR cell signaling pathway to induce proliferation of both porcine and ovine conceptus trophectoderm cells. However, the genomic effects of arginine on trophectoderm cells is unknown. RNA-seq was used for a comparative transcriptome analysis of porcine and ovine trophectoderm cells to further understand effects of Arg on regulation of metabolism in trophectoderm cells. An established porcine trophectoderm (pTr) cell line isolated from D12 porcine conceptuses, as well as an established ovine trophectoderm (oTr) cell line isolated from D15 ovine conceptuses were used to determine response to Arg at the physiological concentration of 0.2 mM in a 48-h culture. In pTr cells, a total of 2,723 differentially expressed genes (DEG; 1,482 up and 1,241 down) were identified in response to Arg. In oTr cells, a total of 5,369 DEG (2,819 up and 2,550 down) were detected. Comparison analyses showed that the Arg-treated pTr and oTr transcriptomes share 873 common DEG (273 up and 342 down). Canonical pathway analyses identified the top enriched pathways in both pTr and oTr cells, including activation of actin cytoskeleton signaling, adrenomedullin signaling, and IGF-1 signaling; and inhibition of cell cycle G2/M checkpoint regulation, and p53 signaling. In response to Arg, pathways associated with cholesterol biosynthesis, and estrogen-mediated S-phase entry were exclusively activated in the pTr cells; whereas interferon signaling, ephrin receptor signaling, and integrin signaling were specifically activated in the oTr cells. Results from this study advance understanding of mechanisms responsible for elongation of ovine and porcine conceptuses and enable the rational design of future experiments.